The Role of Intangible Heritage in Critical Citizenship Education: An Action Research Case Study with Student Primary Education Teachers - Yamilé Pérez-Guilarte; Roberto García-Morís (Education Sciences, 2023)
Heritage plays a significant role in understanding historical societies, particularly intangible heritage, as a legacy kept “alive” solely by the action of communities. Therefore, it holds great education potential in the context of critical citizenship education. This action research aims to investigate the perceptions of primary education teachers about intangible heritage and its didactic potential in critical citizenship education. In addition, this paper analyses the changes and continuities that occur in student teachers’ perceptions after carrying out a didactic project focused on relevant social problems linked to the Way of Saint James. This case study is proposed for primary teachers in initial training at the University of A Coruña (Galicia, Spain). The study was conducted during three academic years (2020–2023), with the participation of 160 student teachers. The questionnaire, the interview, and the focus group were used as research instruments. Students learned to give more importance to understanding intangible heritage and reconsidered it as an educational resource for critical citizenship education. However, many aspects of a traditional heritage education remain, where what matters is to respect and care for what is inherited without questioning its current value or its suitability for transmission to future generations.